Lex Charitatis: A Juristic Disquisition on Law in the Theology of Martin Luther - VanDrunen, David (A journal of church and state, 2010)
This volume presents the first English translation of Johannes Heckel's masterpiece on Martin Luther's understanding of law. The book was first published in West Germany in 1953; the second edition (upon which this translation is based) appeared posthumously in 1973. Though the volume is a hefty tome of 566 total pages, the actual text of Lex Charitatis is a mere 132 pages, thanks to Heckel's concise and lucid style. A series of seven appendices comprise another one hundred pages.